2017
DOI: 10.1186/s40510-017-0181-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the relationship between maxillary incisors and the incisive canal by cone-beam computed tomography in an adult Japanese population

Abstract: BackgroundIn setting goals for orthodontic treatment, determining the morphologies of the alveolar bone and maxillary incisor root is important for avoiding root resorption, dehiscence, and fenestration. This study aimed to analyze the configurational relationships among maxillary incisors, the alveolar border, and the incisive canal by cone-beam computed tomography (CBCT).MethodsCone-beam CT images of 93 orthodontic patients were evaluated for length of the incisive canal (L); angles between the palatal plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…Kotaro et al [15] in their study found out that the average mesiodistal diameter of the incisive fossa was 3.3 mm and 2.8 mm in males and females respectively. Matsumura et al [16] in their study measured it as 3.1 mm and 3.3 mm in males and females respectively. In the present study, the average diameter of the canal at the level of the nasal floor was 1.54 mm and 1.50 mm in males and females respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kotaro et al [15] in their study found out that the average mesiodistal diameter of the incisive fossa was 3.3 mm and 2.8 mm in males and females respectively. Matsumura et al [16] in their study measured it as 3.1 mm and 3.3 mm in males and females respectively. In the present study, the average diameter of the canal at the level of the nasal floor was 1.54 mm and 1.50 mm in males and females respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The incisive canal contains the nasopalatine vessels and nerves, branches of the maxillary division of the trigeminal nerve, and the maxillary artery. 11 12 13 14 The proximity of the maxillary incisor roots to the incisive canal and approximation or invasion of the incisive canal by the tooth roots after anterior tooth retraction has not been evaluated in detail, probably because the incisive canal is a midsagittal structure positioned between the roots, with a morphology and dimension that are not clearly defined on conventional two-dimensional (2D) images. However, the availability of 3DCT has allowed observation of the incisive canal as an anatomical structure that may be associated with orthodontically induced inflammatory root resorption in the maxillary central incisors during maximum retraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the availability of 3DCT has allowed observation of the incisive canal as an anatomical structure that may be associated with orthodontically induced inflammatory root resorption in the maxillary central incisors during maximum retraction. 11 12 13 14 Variations in the morphology of the incisive canal have frequently been reported in 3DCT studies; these include lateral deviation, widening or cystic changes, and furcation, among others. 11 Therefore, evaluation of the “safe zone” (i.e., the area of safe tooth movement within the alveolar bone) using pretreatment 3DCT images may be very important to ensure minimal apical root damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between orthodontic treatment and gingival recession has been controversially discussed in clinical research. Studies have shown that, in patients who exhibit gingival recession caused by occlusal trauma, the alveolar bone is remodeled and the condition of gingival recession is improved by orthodontic treatment [ 10 ]. It has also been reported that the prevalence of gingival recession is increased by orthodontic treatment in patients with mandibular anterior teeth anteversion and in patients requiring upper dental arch expansion.…”
Section: Introductionmentioning
confidence: 99%